The Association Between Dietary Diversity Score and Odds of Diabetic Nephropathy: A Case-Control Study - Rezazadegan, Mahsa; Mirjalili, Fatemeh; Jalilpiran, Yahya; Aziz, Monireh; Jayedi, Ahmad; Setayesh, Leila; Yekaninejad, Mir Saeed; Casazza, Krista; Mirzaei, Khadijeh (Frontiers in Nutrition, 2022)
Dietary diversity score (DDS) may be a useful strategy for monitoring risks associated with chronic diseases. Few studies have investigated the relationship between DDS and the progression to chronic kidney disease. A better understanding of the relationship between DDS and diabetic nephropathy (DN) may provide insight for monitoring the overall diet and clinical outcomes. This case-control study included 105 women with DN and 105 age and diabetes duration-matched controls to evaluate the extent to which DDS is associated with DN. Dietary intake was assessed using food frequency questionnaire (FFQ). DDS was calculated based on the method using five food groups: bread/grains, vegetables, fruits, meats, and dairies. Conditional logistic regression was performed to examine the association between DDS and odds of DN. Anthropometric measures and physical activity levels were evaluated using standard protocols. In fully adjusted model (controlled for age, body mass index, energy intake, physical activity, diabetes duration, cardiovascular disease history, and drug usage), greater adherence (the third vs the first tertile) to DDS (OR= 0.13; 95% CI (0.05-0.35)), vegetables group (OR= 0.09; 95% CI (0.02-0.36)), and fruits group (OR= 0.05; 95% CI (0.01 -0.20)) were significantly associated with lower odds of DN. However, we did not observe any significant relationship between other DDS components and the odds of DN. Our findings showed that higher DDS might be associated with reduced odds of DN. However, more prospective studies are warranted to confirm these findings.